Constructing "Race" and "Ethnicity" in America: Category-Making in Public Policy and Administration - Yanow, Dvora (Routledge, 2003)
What do we mean in the U.S. today when we use the terms "race" and "ethnicity"? What do we mean, and what do we understand, when we use the five standard race-ethnic categories: White, Black, Asian, Native American, and Hispanic? Most federal and state data collection agencies use these terms without explicit attention, and thereby create categories of American ethnicity for political purposes. Davora Yanow argues that "race" and "ethnicity" are socially constructed concepts, not objective, scientifically-grounded variables, and do not accurately represent the real world. She joins the growing critique of the unreflective use of "race" and "ethnicity" in American policymaking through an exploration of how these terms are used in everyday practices. Her book is filled with current examples and analyses from a wealth of social institutions: health care, education, criminal justice, and government at all levels. The questions she raises for society and public policy are endless. Yanow maintains that these issues must be addressed explicitly, publicly, and nationally if we are to make our policy and administrative institutions operate more effectively.